The Association of Metabolic Dysfunction and Mood Across Lifespan Interacts With the Default Mode Network Functional Connectivity - Portugal-Nunes, Carlos; Reis, Joana; Coelho, Ana; Moreira, Pedro Silva; Castanho, Teresa Costa; Magalhães, Ricardo; Marques, Paulo; Soares, José Miguel; Amorim, Liliana; Cunha, Pedro Guimarães; Santos, Nadine Correia; Costa, Patrício; et al. (Frontiers in Aging Neuroscience, 2021)
Background: Numerous studies suggest a relationship between depression and metabolic syndrome, which is likely influenced by age. Interestingly, functional imaging analysis has shown an association between functional connectivity in the default mode network (DMN-FC) and components of metabolic syndrome, which we explore here. Methods: From a larger longitudinal cohort study on healthy aging, 943 individuals were extensively characterized for mood and cognition. Among these, 120 individuals selected as displaying the extreme cognitive performance within the normal range (good and poor performers) were further studied. Here, in a cross-sectional design, using confirmatory factor analysis (CFA), we study the association between metabolic dysfunction and depressive mood as function of age and its relationship with DMN-FC. Results: Metabolic dysfunction was modeled as a second-order latent variable using CFA. First-order latent variables were obesity, glucose dysmetabolism, lipids imbalance and blood pressure. Using multiple linear regression models, we observed that metabolic dysfunction, glucose dysmetabolism and lipids imbalance were linearly associated with depressive mood, and the association with obesity was U-shaped. The association of metabolic dysfunction, obesity, and glucose dysmetabolism with depressive mood is positive for the younger individuals in our sample and vanishes with aging. The FC of the right superior temporal gyrus with the DMN correlated with both obesity and depressive mood. In participants with higher obesity scores, FC increased with higher GDS scores, while in those with lower GDS scores, FC decreased. Age and blood pressure were associated with a more complex pattern of association between FC of the right supramarginal gyrus and GDS score. Conclusion: The association of metabolic dysfunction with depressive mood is influenced by age and relates with differential patterns of DMN-FC. The combination of the effects of age, mood and metabolic dysfunction is likely to explanation of the heterogeneity of DMN-FC, which deserves further investigation with larger and longitudinal studies.